The complete mitochondrial genome of Antheraea proylei strain In981 (Lepidoptera: Saturniidae) - Jian Yang; Ru-Song Zhang; Dong-Bin Chen; Miao-Miao Chen; Yu-Ping Li; Yan-Qun Liu (Mitochondrial DNA. Part B. Resources, 2019)
In the present study, we report the complete mitochondrial genome of Antheraea proylei strain In981, a hybrid of Chinese oak silkmoth (A. pernyi) and Indian oak silkmoth (A. roylei). The circular molecule is 15,573 bp in length, with 37 typical coding genes (13 protein-coding genes, 2 ribosomal RNA genes, and 22 transfer RNA genes) and one non-coding A + T-rich region of 552 bp long. Its gene components and gene order are identical to the common type found in Bombycoidea species. Phylogenetic analyses revealed that In981 is closely related to A. pernyi rather than A. roylei. This is the first report on the complete mitochondrial genome of A. proylei.